Methods of suppressing ion migration in n-i-p perovskite solar cells - Dongmei He; Yue Yu; Xinxing Liu; Xuxia Shai; Jiangzhao Chen (iEnergy)
In the past 10 years, perovskite solar cells (PSCs) have undergone extremely rapid development, with a record certified power conversion efficiency (PCE) of 26.7%, which is very close to the limit efficiency. However, the inherent instability caused by ion migration impedes the realization of long-term operationally stable PSCs. In this review, the types and mechanisms of ion migration occurring in various functional layers of negative-intrinsic-positive (n-i-p) PSCs are summarized. Additionally, methods of suppressing ion migration are systematically discussed. Finally, the prospects of current challenges and future development directions are proposed to advance the achievement of high-performance regular PSCs with high stability and PCE.